"In Italian hand": melancholy, gender and bibliographical codes in commemorative text. Issue 6 (2nd November 2022) - Lauenstein, Eva
ABSTRACT: This essay begins to locate female sadness in the complex popular literary environment of the seventeenth century. It focuses on bibliographical evidence to trace the physical presentation of despair in a set of commemorative pamphlets and canonical early modern theatre by William Shakespeare and John Webster. Doing so, this article aims to give insight into cultural cross-fertilization between popular literary milieus and enrich our understanding of how print conventions shaped and controlled female authorial voices.